2014
DOI: 10.1002/smi.2541
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning, Marital Satisfaction and Social Support in Hemodialysis Patients and their Spouses

Abstract: A growing number of studies have demonstrated the importance of marital quality among patients undergoing medical procedures. The aim of the study was to expand the literature by examining the relationships between stress, social support and family and marriage life among hemodialysis patients. A total of 114 participants, including 38 patients and their spouses and 38 healthy controls, completed a survey package assessing social support, stress, family functioning and marital satisfaction and quality. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 45 publications
4
44
1
1
Order By: Relevance
“…Compared with unmarried adult patients with epilepsy, married adult patients demonstrate higher employment status and the longer course of disease. Since marriage helps foster a sense of meaning, promotes healthy behaviors, reduces risk factors, and enhances adherence to medical regimens,[16] married adult patients with epilepsy have better medication compliance that the nonmarried subgroup. Emotional support received from family members has been found to have positive effects on mental health, family cohesion, and marriage quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with unmarried adult patients with epilepsy, married adult patients demonstrate higher employment status and the longer course of disease. Since marriage helps foster a sense of meaning, promotes healthy behaviors, reduces risk factors, and enhances adherence to medical regimens,[16] married adult patients with epilepsy have better medication compliance that the nonmarried subgroup. Emotional support received from family members has been found to have positive effects on mental health, family cohesion, and marriage quality.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional support received from family members has been found to have positive effects on mental health, family cohesion, and marriage quality. [16] This suggests that marriage is important for patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…People on haemodialysis and their spouses experience higher stress responses and demonstrate lower family adaption than healthy controls (Jiang et al . ). Carers can struggle to be included in treatment decisions and processes and may feel powerless and forgotten by the renal team (Aasen et al .…”
Section: Introductionmentioning
confidence: 97%
“…The experience of conjugal life with suffering in the present study is compatible with the findings of a study in Pakistan, revealing near half of married patients report changes in the partner's behavior after diagnosis of hepatitis (27). A study on hemodialysis patients in China showed that patients and their partners had a great deal of stress and this stress negatively influenced their marital satisfaction (28).…”
Section: Discussionmentioning
confidence: 99%